ABI1‐based expression signature predicts breast cancer metastasis and survival. Issue 14 (26th January 2022) - Regua, Angelina; Papp, Csaba; Grageda, Andre; Porter, Baylee A.; Caza, Tiffany; Bichindaritz, Isabelle; Krendel, Mira; Sivapiragasam, Abirami; Bratslavsky, Gennady; Kuznetsov, Vladimir A.; Kotula, Leszek
Abstract : Despite the current standard of care, breast cancer remains one of the leading causes of mortality in women worldwide, thus emphasizing the need for better predictive and therapeutic targets. ABI1 is associated with poor survival and an aggressive breast cancer phenotype, although its role in tumorigenesis, metastasis, and the disease outcome remains to be elucidated. Here, we define the ABI1 ‐based seven‐gene prognostic signature that predicts survival of metastatic breast cancer patients; ABI1 is an essential component of the signature. Genetic disruption of Abi1 in primary breast cancer tumors of PyMT mice led to significant reduction of the number and size of lung metastases in a gene dose‐dependent manner. The disruption of Abi1 resulted in deregulation of the WAVE complex at the mRNA and protein levels in mouse tumors. In conclusion, ABI1 is a prognostic metastatic biomarker in breast cancer. We demonstrate, for the first time, that lung metastasis is associated with an Abi1 gene dose and specific gene expression aberrations in primary breast cancer tumors. These results indicate that targeting ABI1 may provide a therapeutic advantage in breast cancer patients. Abstract : Breast cancer (BC) remains one of the leading causes of mortality in women worldwide. We identified a set of seven genes that predicted the metastatic potential of primary BC tumors. Additionally, we confirmed the role of ABI1 that we identified as a key prognostic metastatic biomarker, in a mouse model of BC metastasis to the lungs. Our data showed that the ABI1 ‐seven‐gene signature holds prognostic potential and that targeting of ABI1 may provide therapeutic advantage in patients with BC.